Expanding the boundaries of health and social science : case studies in interdisciplinary innovation - Kessel, Frank S.; Rosenfield, Patricia L.; Anderson, Norman B. (Oxford University Press, 2003)
Health psychology has a wide scope, encompassing all influences on behaviour from emotion to overcrowded living situations. This volume articulates both the benefits of interdisciplinary exchange and the best strategies for working together.